UPAYA MENINGKATKAN KOGNITIF ANAK DENGAN MEDIA KINCIR ANGKA DI TK MAYA PERMATA PENYASAWAN PADA USIA 4-5 TAHUN - Harpini Harpini; Rizki Amalia; Putri Asilestari; Zulfah Zulfah; Yusnira Yusnira (Jurnal Dedikasi Pendidikan, 2024)
This reseach describes the lack of children cognitive abilities in recognizing number symbols. For that reason, the use of media is needed to improve their abilities to recognize number symbols by using number wheel media. The objects of this research are to find out the children learning process and their activities in the classrom by using number wheel and to improve the cognitive abilities in recognizing number symbols by using number wheel for students at Maya Permata B Kindergarten. This is an action research that involved 10 students. The data were collected by using observation sheets: check list. There are two main methods of data analysis, they are descriptive qualitative and quantitative techniques. The result of pre-observation showed that only 30,83 % of students are able to recognize number symbols. In the first cycle , there was an increasing percentage (53,33%) and in the cycle 2 , they have reached minimum completness indicator criteria. It was 81,66%. According to the results, it can be concluded that the use of number wheel can improve number symbols of student ability at Maya Permata B Kindergarten.